Esophageal cancer: Outcome and potential benefit of esophagectomy in elderly patients. Issue 19 (24th August 2022) - Laurent, Adeline; Marechal, Raphael; Farinella, Eleonora; Bouazza, Fikri; Charaf, Yassine; Gay, France; Van Laethem, Jean‐Luc; Gonsette, Kimberly; El Nakadi, Issam
Abstract: Background: This analysis evaluated the morbimortality and the potential benefit of esophagectomy for cancer in elderly patients. Methods: Patients who underwent esophagectomy for EC were divided into elderly (≥70 years) and nonelderly (<70 years) groups. The groups were compared regarding patient and tumor characteristics, postoperative morbimortality, and disease‐free, overall and cancer‐specific survival. Results: Sixty‐one patients were classified into elderly, and 187 into nonelderly groups. The elderly were characterized by a higher rate of WHO score ( p < 0.0001), higher cardiac ( p < 0.004) and renal ( p < 0.023) comorbidities. The rate of neoadjuvant therapy and especially of neoadjuvant CRT was significantly lower in elderly patients ( p < 0.018 and p < 0.007). Operative morbidity was also higher in this group ( p < 0.024). The 30‐ and 90‐day mortality was 8.2 and 11.5%, respectively in elderly patients and 0.5 and 3.2% in nonelderly patients ( p < 0.004 and p < 0.012). This 90‐day mortality decreased when specific surgery‐related deaths were taken into consideration. OS and DFS were significantly better in the nonelderly group ( p < 0.003 and p < 0.005) while no difference was observed for cancer‐specific survival (CSS). Conclusion: No difference in CSS was observed. Although elderly patients with EC had higher postoperative morbimortality, the age should not be a criterion whether to perform, or not to perform, esophagectomy. This decision must be based on the balance between the patient's general condition and aggressive disease. Abstract : Cancer specific survival stratified by age.